Exploring new avenues to assess the sharp end of patient safety: an analysis of nationally aggregated peer review data. Issue 12 (26th September 2014) - Meeks, Derek W; Meyer, Ashley N D; Rose, Barbara; Walker, Yuri N; Singh, Hardeep
Abstract : Background: Many healthcare organisations (HCOs) use peer review to evaluate clinical performance, but it is unclear whether these data provide useful insights for assessing the sharp end of patient safety. Objective: To describe outcomes of peer review within the Department of Veterans Affairs (VA) healthcare system and identify opportunities to leverage peer review data for measurement and improvement of safety. Design: We partnered with the VA's Risk Management Program Office to perform descriptive analyses of aggregated peer review data collected from 135 VA facilities between October 2011 and September 2012. We determined the frequency of screening factors used to initiate peer review and processes contributing to substandard care. We also evaluated peer review data for diagnosis-related performance concerns, an emerging area of interest in the patient safety field. Results: During the study period, 23 287 cases were peer reviewed; 15 739 (68%) were sent to local peer review committees for final outcome determination after an initial review and 2320 cases were ultimately designated as substandard care (mean 17 cases/facility). In 20% of cases, the screening source was unspecified. The most common process contributing to substandard care was 'timing and appropriateness of treatment'. Approximately 16% of committee reviewed cases had diagnosis-related performance concerns, which were estimated to occur in approximately 0.5% of total hospital admissions. Conclusions: Peer review may be a useful tool for HCOs to assess their sharp end clinical performance, particularly safety events related to diagnostic and treatment errors. To address these emerging and largely preventable events, HCOs could consider revamping their existing peer review programmes to enable self-assessment, feedback and improvement.